Analisis Perbandingan Tingkat Kesegaran Jasmani Mahasiswa di Universitas Cokroaminoto Palopo - Nuryanti Nuryanti (Universitas Cokroaminoto Palopo, 2018)
This study aims to obtain answers to the problems: about whether there is a difference in the level of physical fitness between students of PGSD class I and students of PGSD class K at Cokroaminoto University. The population of this study was all students in PGSD I and PGSD K classes aged 16-19 years. The type of approach used is descriptive research, and the research instrument is: Physical fitness level test. Processing of research data is using descriptive statistics using the t test. by using a significant level of α 0.05. The following data can be obtained: that there are differences in physical fitness between PGSD I and PGSD K at Cokroaminoto University.